Perceptions of Educational Barriers Affecting the Academic Achievement of Latino K-12 Students. - Becerra, David (Children & Schools, 2012)
This study examined different factors affecting the perceptions of bamers in academic achievement of Latino K-12 students. The study used data from 1,508 participants who identified themselves as being of Hispanic or Latino heritage in the 2004 National Survey of Latinos: Education, compiled by the Pew Hispanic Center between August 7 and October 15, 2003, to study respondents' attitudes toward education. Results indicated that higher levels of income, education, and linguistic acculturation were associated with the perception of barriers in education for Latino students. Althou.gh six potential barriers were explored, the barriers identified by the participants as reasons why Latino students do not perform as well as white students were that "Schools are too quick to label Latino students as having behavior/learning problems"; "White teachers don't understand Latino culture"; and "Latino parents neglect to push their kids to work hard." Implications for school social work practice are discussed.